Croatian American Literature as a Transculturated Discourse - Šesnić, Jelena (Array, 2013)
Building on paradigms provided in social sciences, ethnology and political theory in particular, the article proposes to analyze specific non-fictional writings by Croatian and Croatian American authors as instances of a transculturated discourse spanning at least two cultural contexts, addressing multiple audiences and implying a transnational horizon of production and reception. Additional categories borrowed from ethnography are used in order to account for the complexity of these and similar texts, such as the semiotic turn, auto-ethnography, diaspora, participant observation, and the like. Elements of postcoloniality and orientalizing strategies are detected in the texts by Ante Tresić Pavičić and Josip Novakovich but the overall argument contends that by virtue of strategies of transculturation the texts evade historical and political strictures specifically.